Genetic Characterization of the Belgian Nephropathogenic Infectious Bronchitis Virus (NIBV) Reference Strain B1648 - Vishwanatha R.A.P. Reddy; Sebastiaan Theuns; Inge D.M. Roukaerts; Mark Zeller; Jelle Matthijnssens; Hans J. Nauwynck (Viruses, 2015)
The virulent nephropathogenic infectious bronchitis virus (NIBV) strain B1648 was first isolated in 1984, in Flanders, Belgium. Despite intensive vaccination, B1648 and its variants are still circulating in Europe and North Africa. Here, the full-length genome of this Belgian NIBV reference strain was determined by next generation sequencing (NGS) to understand its evolutionary relationship with other IBV strains, and to identify possible genetic factors that may be associated with the nephropathogenicity. Thirteen open reading frames (ORFs) were predicted in the B1648 strain (51UTR-1a-1b-S-3a-3b-E-M-4b-4c-5a-5b-N-6b-31UTR). ORFs 4b, 4c and 6b, which have been rarely reported in literature, were present in B1648 and most of the other IBV complete genomes. According to phylogenetic analysis of the full-length genome, replicase transcriptase complex, spike protein, partial S1 gene and M protein, B1648 strain clustered with the non-Massachusetts type strains NGA/A116E7/2006, UKr 27-11, QX-like ITA/90254/2005, QX-like CK/SWE/0658946/10, TN20/00, RF-27/99, RF/06/2007 and SLO/266/05. Based on the partial S1 fragment, B1648 clustered with the strains TN20/00, RF-27/99, RF/06/2007 and SLO/266/05 and, further designated as B1648 genotype. The full-length genome of B1648 shared the highest sequence homology with UKr 27-11, Gray, JMK, and NGA/A116E7/2006 (91.2% to 91.6%) and was least related with the reference Beaudette and Massachusetts strains (89.7%). Nucleotide and amino acid sequence analyses indicated that B1648 strain may have played an important role in the evolution of IBV in Europe and North Africa. Further, the nephropathogenicity determinants might be located on the 1a, spike, M and accessory proteins (3a, 3b, 4b, 4c, 5a, 5b and 6b). Overall, strain B1648 is distinct from all the strains reported so far in Europe and other parts of the world.